Analyzing Syntactic Categories and Grammatical Functions in English Sentences - Sharma, Lok Raj (International Research Journal of MMC, 2026)
It is essential for language learners to decode how meaning is organized and conveyed in English sentences. This study adopted a qualitative documentary research design to explore syntactic structures in English sentences. The objective of the study is to analyze syntactic categories and grammatical functions that operate within English sentence structures. Qualitative secondary data were collected from books and journal articles related to syntax and grammatical analysis. The data were gathered through a comprehensive review of secondary sources relevant to syntactic theory and sentence structure. The collected data were analyzed using structural analysis to identify patterns of syntactic categories and their grammatical roles. The analysis revealed that English sentences are primarily organized around core syntactic categories such as noun phrases, verb phrases, prepositional phrases, adjective phrases, and adverbial phrases. It was found that these categories perform grammatical functions including subject, predicate, direct object, indirect object, complement, and adjunct within sentence structures. These patterns demonstrate how syntactic categories combine with grammatical functions to form meaningful sentence structures. The findings highlight the systematic relationship between syntactic structure and grammatical roles in English, contributing to a clearer understanding of sentence construction in English grammar. This study is significant because it enhances understanding of how syntactic categories and grammatical functions operate in English sentence structure, helping to clarify the relationship between phrase types and their roles in communication. The findings benefit linguists, English language teachers, students of linguistics, and researchers interested in syntax and language structures. It is essential for language learners to decode how meaning is organized and conveyed in English sentences. This study adopted a qualitative documentary research design to explore syntactic structures in English sentences. The objective of the study is to analyze syntactic categories and grammatical functions that operate within English sentence structures. Qualitative secondary data were collected from books and journal articles related to syntax and grammatical analysis. The data were gathered through a comprehensive review of secondary sources relevant to syntactic theory and sentence structure. The collected data were analyzed using structural analysis to identify patterns of syntactic categories and their grammatical roles. The analysis revealed that English sentences are primarily organized around core syntactic categories such as noun phrases, verb phrases, prepositional phrases, adjective phrases, and adverbial phrases. It was found that these categories perform grammatical functions including subject, predicate, direct object, indirect object, complement, and adjunct within sentence structures. These patterns demonstrate how syntactic categories combine with grammatical functions to form meaningful sentence structures. The findings highlight the systematic relationship between syntactic structure and grammatical roles in English, contributing to a clearer understanding of sentence construction in English grammar. This study is significant because it enhances understanding of how syntactic categories and grammatical functions operate in English sentence structure, helping to clarify the relationship between phrase types and their roles in communication. The findings benefit linguists, English language teachers, students of linguistics, and researchers interested in syntax and language structures.